Utilization of the Topoclimatic Viticultural Potential in Haloze - Žiberna, Igor (Podeželje, 2026)
The chapter discusses the relationship between the highest quality topoclimatic viticultural locations and the actual land use in these areas, regarding viticultural areas. The topoclimatic characteristics for the needs of viticulture depend mainly on the slope and exposure of the slope, which affects global solar radiation, and the relative height, which determines the frequency of occurrence of low temperatures and frost, which are unfavorable phenomena for the vine. From the point of view of topoclimatic characteristics, we have classified Haloze into four classes and then analyzed the land use in the highest quality locations and changes in land use in these locations, based on which we also determine the utilization of the topoclimatic viticultural potential in Haloze in the period 2000-2025.